Continuing Professional Development (CPD) melalui Webinar dan Kompetensi Perawat - Yuliana Bernadetta; Rr. Tutik Sri Hariyati; Hening Pujasari (Jurnal Keperawatan Silampari, 2023)
This study aims to identify the competence of nurses after participating in CPD and the process of implementing CPD. The research method uses a quantitative descriptive method with a cross-sectional approach. The analysis results show a significant relationship between Continuing Professionalism Development (CPD) through webinars and nurse competence (p = 0.000). This study found that from the nurse's characteristics, only the level of education influenced the activities to take part in CPD through the webinar, a value of p < 0.05. In contrast, the other nurses' characteristics had no effect. In conclusion, nurse characteristics and CPD implementation activities affect the competencies obtained only by 46.4%, and factors outside of nurse characteristics influence the rest. Keywords: CPD, Nurse Competency, Webinar